Eastern wall of the Garbhagriha of the Kaner-ki-Putli Temple - Temples of India Project Team (Jio Institute, 2024)
On the rear (eastern) wall of the garbhagriha (sanctum sanctorum) of the Kaner-ki-Putli Temple, one can observe an empty central niche, surrounded by the dikapalas (deities of the cardinal directions), Indra and Ishana in graceful poses, along with Shaiva ascetics and the surasundari (celestial damsels) standing in elegant poses.